Pharmacology, Systematic Review and Recent Clinical Trials of Metadoxine - Di Miceli, Mathieu; Gronier, Benjamin (Reviews on Recent Clinical Trials, 2018)
Background: Metadoxine is composed of pyroglutamic acid and vitamin B6. Administrations of metadoxine are indicated in cases of acute alcohol intoxication or in chronic alcoholism. Objectives: To reference all available clinical trials investigating the effects of metadoxine on humans. A focus was put on alcohol intoxication and chronic alcoholism, alcohol abstinence and survival rates. Adverse events were also taken into consideration. Finally, potential roles of metadoxine in treating disorders of the central nervous system will be assessed. Methods: PRISMA guidelines were followed. Computerised literature searches were performed in July 2017 to retrieve all clinical trials investigating metadoxine from the MEDLINE®, the European Union Clinical Trials Register and the ClinicalTrials.gov databases, using the following equation: “metadoxine”. Inclusion criteria were all published clinical trials investigating metadoxine in humans, regardless of outcome measures. Exclusion criteria were articles not abstracted, in vitro studies, studies in rodents, retrospective studies and reviews. Results: Sixteen studies were included. Evidence suggests that metadoxine appears safe to use, as it rarely induced adverse events (reported in 7 out of the 7 studies measuring safety/tolerability). Moreover, metadoxine seems efficient in treating acute alcohol intoxication (2/2 studies) as well as improving liver functions following chronic alcoholism (4/5 studies). Finally, currently on-going clinical trials will reveal if metadoxine could be indicated in attention deficit and hyperactivity disorders as well as fragile X syndrome. Conclusion: Metadoxine appears safe to use and seems efficient to improve liver functions following alcohol-related diseases. Further clinical trials will be necessary to determine if metadoxine can be promising for treating brain disorders. PROSPERO registration number: CRD42017072964.
Keywords: fragile X syndrome